A Review on Anti-diabetic Plants - Qais, Nazmul; Jahan, Sadia; Shajib, Md Shafiullah (Dhaka University Journal of Pharmaceutical Sciences, 2018)
Diabetes mellitus is a common metabolic disorder whose prevalence is rapidly increasing all over the world. According to WHO, diabetes will be the seventh leading cause of death in 2030. Since long back, plants have been used to heal or combat illness and are the source of many modern medicines. In view of the above aspects, the present review provides information about the antidiabetic plants, available through literature source from various database. From the present study it is evident that most of the plants having anti-diabetic properties belong to the family Moraceae, Cucurbitaceae, Liliaceae, Anacardiaceae, Myrtaceae, Fabaceae, Solanaceae, Asteraceae and many others. The hypoglycemic activities are contained in different parts of these plants like leaf, rhizomes, fruits, bark, seeds or other parts which differ from species to species. It is also evident from this review that the mode of action and dosage of administration differs from plant to plant. Dhaka Univ. J. Pharm. Sci. 17(1): 139-152, 2018 (June)